O exercício materno e paterno em casos de crianças com deficiência auditiva - Zanini, Angélica Costa (2014)
This study aims to know how works the paternal and maternal role of children with hearing impairment . As well as, it has analized if there is any difficulty in the development of those roles, and this way to know the parent s view about hearing loss. The research was qualitative, contemporary, cross and aplied character. It was carried out at SAF (Speech -Language Service at UFSM( Federal University of Santa Maria ) . From 23 children who have been seen at Habilitation and Rehabilitation Sector. It was conducted interviews with parents of 13 children, totaling 15 interviewed. Of those, there were 10 mothers, 4 fathers, and one grandmother. Most interviews were conducted only with mothers because most fathers did not want to be part of the study. They were semi-structured interviews , the ones were recorded and later transcribed. Data were analyzed from the perspective of Bardin (1977). The parents received the feedback of each interview. As result, it was realized certain difficulties of some parents in performing their respective roles. It was verified that some fathers, mothers and caregivers did not support their roles facing the difficulty of dealing with a child with hearing impairment, because it is not the image of the ideal child. It was noticed that the biggest problem was about the failure in mother role, because she neither has played her role nor has allowed that the father has had a role in mother and child relationship. Some parents have difficulty in set limit. About hearing loss results indicate that most parents clash with the diagnosis and react according to their psychological resources and elaboration mourning, as denying it. In conclusion it is expected that new studies are conducted involving a connection between Speech Language Therapy and Psychology in relation to theme.